PREVENTION OF ANEMIA IN PREGNANT WOMEN THROUGH GIVING CATFISH CRACKERS AND MORINGA LEAVES - Eka Sarofah Ningsih; Kustini Kustini; Lailatul Fadliyah; Shelin Elsza Putri (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
The high risk of morbidity and mortality in mother and baby can be caused by anemia. Pregnant women are vulnerable to nutritional problems and other diseases, including infection with the Covid-19 virus. One of the preventive measures is to consume nutritious foods such as food sources of antioxidants. Giving Crackers Catfish and Moringa Leaves is expected to overcome the incidence of anemia in pregnant women. The purpose of this study was to determine the prevention of anemia in pregnant women through the provision of catfish crackers and Moringa leaves. This research will use quantitative research with a pre-experimental design. This research was conducted in the Kedanyang Sub-Puskesmas area in 2022. The research subjects were pregnant women with anemia at the Kedanyang Sub-Puskesmas (Hb<11 g/dl) (n=27), obtained by simple random sampling. The expected outcome is to prevent the incidence of anemia in pregnant women and to publish the proceedings of an international.